The Role of Character Education in Elementary Schools in the Digital Era - Syifa Salsabila Mahmuddah; Junaidi (Universitas Pendidikan Ganesha, 2025)
Character education in primary schools has a strategic role in shaping students' personalities from an early age, especially amid the challenges of the digital era. This study aims to analyze the role of character education in primary schools in facing the development of digital technology and explore effective strategies for its integration. The method used was a systematic literature review of relevant articles within the 2019-2024 timeframe. Researchers collected journal articles from Google Scholar, Sinta, SemanticScholar. The data analysis technique used was quantitative descriptive obtained from 10 articles that were in accordance with the research study. The results of the analysis show the importance of collaboration between teachers, parents and the community in instilling values such as honesty, responsibility and discipline. Technology has the potential to support character education through interactive learning media, but also presents challenges such as gadget addiction and cyberbullying. For this reason, wise supervision, strengthening digital literacy, and integration of character values into the curriculum and extracurricular activities are needed. In conclusion, character education must be adaptive to technological developments and supported by the synergy of various parties to form a moral and resilient young generation in facing the digital era.